How do you solve #13- 3p = - 5( 3+ 2p )#?

2 Answers
Jun 29, 2018

Answer:

#p = -4#

Explanation:

#13 - 3p = -5(3+2p)#

First, use the distributive property (shown below) to simplify #-5(3+2p)#:
cdn.virtualnerd.com

Following this image, we know that:
#color(blue)(-5(3+2p) = (-5 * 3) + (-5 * 2p) = -15 - 10p)#

Put it back into the equation:
#13 - 3p = -15 - 10p#

Add #color(blue)(10p)# on both sides of the equation:
#13 - 3p quadcolor(blue)(+quad10p) = -15 - 10p quadcolor(blue)(+quad10p)#

#13 + 7p = -15#

Subtract #color(blue)13# from both sides:
#13 + 7p quadcolor(blue)(-quad13) = -15 quadcolor(blue)(-quad13)#

#7p = -28#

Divide both sides #color(blue)7#:
#(7p)/color(blue)7 = (-28)/color(blue)7#

Therefore,
#p = -4#

Hope this helps!

Aug 5, 2018

Answer:

#p=-4#

Explanation:

We can distribute the #-5# on the right to get

#-3p+13=-15-10p#

We can start by adding #10p# to both sides to get

#7p+13=-15#

Next, to get our constants on one side, we can subtract #13# from both sides. We now have

#7p=-28#

To completely isolate the #p# term, we can divide both sides by #7#. We get

#p=-4#

Hope this helps!